The GA 20-Oxidase Encoding Gene MSD1 Controls the Main Stem Elongation in Medicago truncatula - Li, Wanying; Ma, Qingxia; Yin, Pengcheng; Wen, Jiangqi; Pei, Yanxi; Niu, Lifang; Lin, Hao (Frontiers in Plant Science, 2021)
Plant height is an important agronomic trait that is closely related to biomass yield and crop production. Legumes comprise one of the largest monophyletic families that are second only to grasses in terms of economic and nutritional values. However, due to an ancient genome duplication event, most legume plants have complex genomic structures, the molecular mechanisms that determine plant height in legumes remain elusive. Here, we report the identification and characterization of Main Stem Dwarf1 (MSD1), which is required for the plant height in the model legume Medicago truncatula. Loss of function of MSD1 leads to severely reduced main stem height but normal lateral branch elongation in M. truncatula. Histological analysis revealed that the msd1-1 main stem has shorter internodes with reduced cell size and number compared with the wild type, indicating that MSD1 affects cell elongation and cell proliferation. MSD1 encodes a putative GA20 oxidase that is highly expressed in the main shoot apex, but weakly detected in the lateral shoot apices, suggesting that MSD1 expression is associated with its effect on the main stem elongation. HPLC-MS analysis showed that GA9 and GA4, two identified products of the GA20 oxidase, were severely reduced in msd1-1, and the dwarf phenotype of msd1-1 could be rescued by supplementation with gibberellic acid GA3, confirming that MSD1 functions as a biologically active GA20 oxidase. Moreover, we found that disruption of either MtGA20ox7 or MtGA20ox8, homologues of MSD1, has little effects on the elongation of the main stem, while the msd1-1 mtga20ox7-1 mtga20ox8 triple mutants exhibits a severe short main shoot and lateral branches, as well as reduced leaf size, suggesting that MSD1 and its homologues MtGA20ox7 and MtGA20ox8, redundantly regulate M. truncatula shoot elongation and leaf development. Taken together, our findings demonstrate the molecular mechanism of MSD1-mediated regulation of main stem elongation in M. truncatula and provide insights into understanding the functional diversity of GA20 oxidases in optimizing plant architecture in legumes.